2015
DOI: 10.1093/jxb/erv156
|View full text |Cite
|
Sign up to set email alerts
|

Repeat length variation in the 5ʹUTR ofmyo-inositol monophosphatase gene is related to phytic acid content and contributes to drought tolerance in chickpea (Cicer arietinumL.)

Abstract: Myo-inositol metabolism plays a significant role in plant growth and development, and is also used as a precursor for many important metabolites, such as ascorbate, pinitol, and phytate. Phytate (inositol hexakisphosphate) is the major storage pool for phosphate in the seeds. It is utilized during seed germination and growth of the developing embryo. In addition, it is implicated in protection against oxidative stress. In the present study, a panel of chickpea accessions was used for an association analysis. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 46 publications
2
37
0
Order By: Relevance
“…Microsatellite repeats, especially the (CT) n motifs, are known to exist in abundance in the 5′UTRs of several eukaryotic genes including plants 5 6 7 35 . However, the involvement of the microsatellite motif per-se or based on their length variation, in transcriptional regulation is only beginning to be investigated in plants 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microsatellite repeats, especially the (CT) n motifs, are known to exist in abundance in the 5′UTRs of several eukaryotic genes including plants 5 6 7 35 . However, the involvement of the microsatellite motif per-se or based on their length variation, in transcriptional regulation is only beginning to be investigated in plants 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In another study, a polymorphic (CT) n microsatellite identified in the 5′UTR region of the wx gene of rice 21 was correlated with amylose content and microsatellite length polymorphism was thought to affect the expression of the related genes of amylose synthesis 22 . Recently, Joshi-Saha and Reddy 23 have suggested that (CT) n repeat length variation in 5′-UTR of the chickpea myo-inositol monophosphatase gene ( CaIMP ), might regulate phytic acid levels to confer drought tolerance in natural populations of chickpea. Additionally, at the whole genome level it has been shown that ~10% of 5′ non-coding CT/GA and CTT/GAA repeats are conserved in Arabidopsis and are thought to be involved in regulation of gene expression in plant-specific pathways 6 .…”
mentioning
confidence: 99%
“…GSH content was measured using a fluorometer and reverse-phase liquid chromatography as per Lu et al (1998), Cairns et al (2006), and Dragičević et al (2015). The phytic acid was estimated in accordance with Gao et al (2007) and Joshi-Saha and Reddy (2015). Amino acid content was calculated using the amino acid analyzer chromatography and UltraViolet-Visible spectrophotometric methods as previously described in Moore et al (1958), Ohkama-Ohtsu et al (2007), and Okoronkwo et al (2017).…”
Section: Subcellular Localizationmentioning
confidence: 99%
“…Higher expressing of CaIMP gene has been shown to improve tolerance to drought. 60 In our previous study, we have shown that BABA pretreatment could signicantly alleviate drought stress impact on maize seedlings. 9 Overexpression of inositol monophosphatase 3 in BABA-primed leaves (ZmSF) as revealed in SSH forward library and validated through qRT-PCR might contribute to drought stress acclimation.…”
Section: Discussionmentioning
confidence: 97%